Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Anggota Satuan Reserse Kriminal Polres Boven Digoel - Ulukyanan, Hagai Fernando; Ridwan, Ridwan; Niar, Hikma (Patria Artha Management Journal, 2025)
This study aims to determine the factors that influence the performance of members of the Criminal Investigation Unit of the Boven Digoel Police. Data analysis used is descriptive statistical analysis and multiple linear regression analysis. The sampling technique in this study applies a data collection method through a questionnaire. The sample obtained and used was 24 respondents from the Criminal Investigation Unit of the Boven Digoel Police. The results of the study indicate that workload does not significantly affect the performance of members of the Criminal Investigation Unit of the Boven Digoel Police, work stress does not significantly affect the performance of members of the Criminal Investigation Unit of the Boven Digoel Police, and job satisfaction significantly affects the performance of members of the Criminal Investigation Unit of the Boven Digoel Police. Meanwhile, the results of the study simultaneously indicate that workload, work stress and job satisfaction simultaneously affect the performance of members of the Criminal Investigation Unit of the Boven Digoel Police.